Hydration status of 2017 Malaysian Agong Cup Rugby Referees / Muhammad Hafizuddeen Bahari - Bahari, Muhammad Hafizuddeen (Faculty of Sport Science and Recreation, 2018)
The purpose of this study was to determine the hydration status of 2017 Malaysian Agong Cup rugby referees based on parameters set which are bodyweight changes, urine specific gravity (uSa), urine pH value (uPH), and urine colour pre and post match as well as the sweat rates data post-match. There were six (N=6) referees partaken in this study. Bodyweight changes, usa, uPH and urine colour were measured before and after each match took place whereas sweat rates was calculated after each match. (Mean ± SD) of pre-match bodyweight changes, usa, uPH and urine colour were (71.35 kg ± 3.95), (1.015 ± .00), (5.67 ± 1.03) and (6 ± 1.84) respectively. (Mean ± SD) of post-match bodyweight changes, usa, uPH, urine colour and sweat rates were (69.65kg ± 3.63), (1.016 ± .01), (4.83 ± .41), (6 ± 2.79) and (1.86 L ± .90) respectively. Results from paired sample tests of bodyweight changes and usa data showed significant differences in between pre and post-match whereas uPH and urine colour data showed no significant differences in between pre and post-match. To conclude, from mean data of bodyweight changes showed 2.38% of decrement in bodyweight changes, whereas for usa, uPH and urine colour mean data showed that the referees started the match with minimal dehydration based on the scale of each parameters and the sweat rates data showed that referees should at least replenish 1.86L of fluid after match to level out the fluid loss during the match.